Physician's InterventionWith the HIV Carrier in an Out-patient Context (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
This study analyzed the doctor-patient relationship in the first consultation after the diagnosis of presence of the virus HIV. The data were collected in observations of video records. The verbal and non-verbal responses of four doctor-patient relationships were analyzed in an out-patient context of a specialized hospital. The responses of the members were analyzed in relation to the function potentially facilitative or non-facilitative to the adhesion to the suitable treatment. It was observed that the doctors' verbal behaviors considered as adhesion facilitators occurred less frequently than the not adhesion facilitators. Their non-verbal behaviors considered adhesion facilitators occurred much more frequently than the non facilitators. The patients presented very more verbal behaviors indicating adhesion than no adhesion. Their non-verbal behaviors adhesion indicative happened a little more than the indicative of no adhesion.